Can a Narrow Frequency Allocation Improve Speech Perception in Korean Cochlear Implant Users? - Choi, Soo Jeong; Park, Bongil; Lee, Sun-Uk; Chang, Jiwon; Im, Gi Jung; Park, Euyhyun (Journal of audiology & otology, 2025)
Background and Objectives: Frequency allocation is crucial in cochlear implantation (CI) mapping, significantly impacting speech perception. Previous studies have suggested that limiting the upper frequency range may improve outcomes; however, evidence remains limited, particularly among non-English-speaking populations. Therefore, this study investigated the relationship between frequency allocation and speech perception in Korean CI users.Subjects and Methods: We prospectively evaluated 14 ears from nine Korean CI users under two frequency allocation conditions: a standard setting (188-7,938 Hz) and a narrow, modified setting (188-5,938 Hz). Speech perception was assessed using Ling’s six-sound test, as well as vowel, consonant, monosyllabic, disyllabic, and sentence recognition tests. Data were analyzed using linear mixed-effects models to account for repeated measures and subject-level clustering.Results: Narrow frequency allocation significantly improved the perception of vowels (p=0.032), consonants (p=0.035), and monosyllables (p=0.022). Disyllable perception exhibited a positive trend (p=0.056), whereas sentence recognition demonstrated no significant difference (p=0.367).Conclusions: Narrow frequency allocation significantly enhanced vowel, consonant, and monosyllable perceptions among Korean CI users. These findings underscore the importance of tailoring CI frequency settings to the phonemic characteristics unique to Korean-speaking populations.